2014
DOI: 10.22158/jbtp.v2n1p84
|View full text |Cite
|
Sign up to set email alerts
|

Testing The Random Walk (Rw) Behaviour of Botswana’s Equity Returns

Abstract: This paper examines the efficiency of Botswana's capital market by testing the presence of random walk (RW) behavior in the Domestic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In Botswana, a study on market efficiency was done on capital markets (Radikoko, 2014) Efficiency of foreign exchange markets has been extensively tested using different econometric techniques and for different years. Most of these tests were however, in developed countries and it was concluded that the markets are efficient.…”
Section: Review Of Previous Studiesmentioning
confidence: 99%
“…In Botswana, a study on market efficiency was done on capital markets (Radikoko, 2014) Efficiency of foreign exchange markets has been extensively tested using different econometric techniques and for different years. Most of these tests were however, in developed countries and it was concluded that the markets are efficient.…”
Section: Review Of Previous Studiesmentioning
confidence: 99%
“…The authors found positive correlations for some companies though there was a negative correlation for others. Subha and Nambi [14] also investigated the predictability of the direction of the stock market using past stock market movement data and they concluded that the K-Nearest neighbour performed well in their classification. For the purposes of this paper, we adopt their approach of using machine learning and using social media data to predict the direction of the stock market price changes .…”
Section: Stock Market and Social Mediamentioning
confidence: 99%